IMPLEMENTASI SISTEM PEMBELAJARAN DARING BERBANTUAN EDMODO PADA MAHASISWA - Ade Mirza (UNIVERSITAS TANJUNGPURA, 2020)
This research is a case study which aims to examine and describe the learning independence, learning outcomes, and student responses to the implementation of lectures with the edmodo-assisted online learning sistem. The subjects of this study were 142 students of the Mathematics education program FKIP Untan Pontianak in 2020 that who programmed the differential calculus course. This research activity in the process involves three senior students as collaborators (research assistants). Lecture practice is carried out by the lecturer who teaches these courses. This research procedure consists of: (1) reviewing the material, preparing research tools and instruments (developing and standardizing instruments). (2) Conducting lectures using the online learning sistem assisted by Edmodo. (3) Distributing questionnaires to obtain independence data, providing learning outcomes tests, and providing questionnaires to get student responses to the implementation of learning - (data collection). (4) Conduct studies and interpretations of the data obtained. (5) Reporting. The results of this study indicate that the learning independence of students in lectures is still not satisfactory. Student responses to the learning sistem were 57.04% giving positive responses, and 42.96% giving negative responses. For learning outcomes, 74.65% were able to achieve a score ≥ 70 and no one got a score less than 60. In this case 57.75% got a B grade and 16.90% got an A. It is clear that learning with the edmodo-assisted online sistem is able to make a fairly good contribution to differential calculus lectures.Key words: Calculus, Independence learning, Mathematics